Modeling surface disinfection kinetics of fresh tomato (Lycopersicum esculentum) using chlorine solutions - Solano Cornejo, Miguel Ángel (2013)
Fresh tomatoes Italian variety were subjected to surface disinfection processes using calcium hypochlorite solutions to determine their germicidal efficiency and kinetics that governs the surface inactivation process in aerobic mesophilic bacteria, yeasts and molds. Chlorine as surface disinfectant was effective against aerobic mesophilic bacteria, yeasts and molds in this order, the resistance of aerobic mesophilic bacteria, yeasts and molds of their values expressed in zchlorine was 455, 500 and 625 ppm respectively. Aerobic mesophilic bacteria present in the tomato surface show a higher resistance to chlorine disinfection according contact time germ- tomato skin is greater due to a better adherence to the tomato skin making it difficult for the action of chlorine on germs; this effect is not present in the case of yeasts or molds. Experimental Dchlorine 20°C values and Dchlorine_20°C values predicted by the First Bigelow’s Model were fit with a correlation of between 0.91 and 0.99. The experimental zchlorine values and values zchlorine predicted by the Second Bigelow’s Model were adjusted with a correlation of 0.72 to 0.86. The variability in the values zchlorine was because germs analyzed to validate the proposed model were composed of various genera. So, the Bigelow’s Method applied to inactivation kinetics of surface chlorine was validated.